Genetic identification of mutations and MLST types associated with decreased susceptibility to ceftriaxone in Neisseria gonorrhoeae - Zhang, Xin; Wang, Hairui; Gu, Yixin; Chen, Xiaoli; Zhou, Guilan; Liu, Chang; Ji, Liyin; Xie, Rui; Zhang, Jianzhong; Shao, Zhujun; Zhang, Maojun (Frontiers in Microbiology, 2026)
Antimicrobial resistance (AMR) in Neisseria gonorrhoeae severely limits treatment options, with increasing resistance even to first-line and last-line ceftriaxone (CRO), posing a major global public health threat. In this study, we systematically identified 53 significantly different mutations between ceftriaxone-resistant and susceptible strains in multiple proteins through bioinformatics analysis. Among these, 33 mutations were identified for the first time, notably including the PorB Q143K via structural analysis. Minimum spanning tree (MST) analysis based on these mutations marked improved sensitivity and specificity for identifying ceftriaxone-resistant strains compared to traditional sequence typing of PenA, PonA, PorB, and MtrR (68.4% vs. 53.2%; 77.3% vs. 57.5%, respectively). Furthermore, analysis of PenA sequences from global 8,325 strains (470 MLST types) revealed that mutation frequencies at key PenA sites are highly associated with MLST types, with 34 high-frequency MLST types (STs) identified. The proportions of these 34 STs were 88.38% in 611 decreased susceptibility to ceftriaxone (CRO-DS) strains and 33.09% in 8,325 background strains, respectively, revealing an extremely significant association between 34 high-frequency STs and CRO-DS (P < 0.0001). In conclusion, this work provides further insights into the molecular mechanisms of CRO resistance while offering significant value for monitoring and predicting emerging CRO-DS-associated MLST types.